1974
DOI: 10.1161/01.res.34.5.711
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Left Ventricular Preload and Afterload by Quantitative Echocardiography in Man

Abstract: Left ventricular circumferential wall stress at end-diastole (preload) and at the end of isovolumic left ventricular contraction (afterload) was calculated in 48 subjects with chronic myocardial and valvular heart disease by using left ventricular internal dimensions and wall thickness measured by quantitative echocardiography, left ventricular end-diastolic pressure, and aortic end-diastolic pressure. These calculations were then compared with similar determinations made using quantitative angiocardiography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 49 publications
4
15
0
Order By: Relevance
“…The Laplace relation, however, implies that wall stress would be reduced only in proportion to the decrease in left ventricular linear dimensions (such as the end-diastolic or end-systolic dimension) and not in proportion to the (much larger) associated decrease in left ventricular volume. Similar conclusions may be derived from calculations directly relating circumferential wall stress and left ventricular echocardiographic dimensions (Ratshin et al, 1974).…”
Section: Implications Relating To Antianginal Efficacy Of Glyceryl Trsupporting
confidence: 73%
“…The Laplace relation, however, implies that wall stress would be reduced only in proportion to the decrease in left ventricular linear dimensions (such as the end-diastolic or end-systolic dimension) and not in proportion to the (much larger) associated decrease in left ventricular volume. Similar conclusions may be derived from calculations directly relating circumferential wall stress and left ventricular echocardiographic dimensions (Ratshin et al, 1974).…”
Section: Implications Relating To Antianginal Efficacy Of Glyceryl Trsupporting
confidence: 73%
“…Recently, Ratshin, Rackley, and Russell have reported (34) on the use of a combined hemodynamic and ultrasonic technique, similar to that used in our study, for the measurement of LV wall stress. In their study close correlation was demonstrated between wall stresses calculated from biplane angiographic and ultrasonic techniques.…”
Section: Resultsmentioning
confidence: 95%
“…The reliability of the echogram in estimating the internal LV minor axis, wall thickness, and circumferential wall stress has recently been demonstrated.9 10 All measurements were processed by the programmed calculator, and time plots of endocardial VCF, midwall VCF, and LV hoop stress were constructed ( fig. 1).…”
Section: Measurements and Calculationsmentioning
confidence: 99%